Adiponectin, Interleukin-18 (IL-18), and Visceral Adipose Tissue in Filipino Americans: Biomarkers and Risk of Type 2 Diabetes - Julian L. Gallegos PhD, MBA, FNP-BC, CNL, FAUNA; Ruth E. Taylor-Piliae PhD, RN, FAHA, FAAN; Thaddeus W. W. Pace PhD; Matthew J. Gallek PhD, RN; Leslie Ritter PhD, RN, FAHA, FAAN (SAGE Publishing, 2024)
Introduction Filipino Americans (FAs) are at high risk for developing type 2 diabetes despite other Asian phenotypes. Evidence suggests that pro-inflammatory interleukin-18 (IL-18) and anti-inflammatory adiponectin biomarkers associated with visceral adipose tissue (VAT) may explain this risk. Objectives This study aimed to quantify the biomarkers in relation to standard ranges of VAT or typical circulating concentration ranges reported in the literature of IL-18 and adiponectin, examine relationships of these markers, and determine if they were different among those participants without diabetes, prediabetes, and diabetes. Methods A cross-sectional study was used to enroll FAs without diabetes, prediabetes, or diabetes. VAT was measured using the InBody 570 © Body Composition Analyzer. Blood samples were obtained to assess plasma concentrations of IL-18 and adiponectin using enzyme-linked immunosorbent assay. All analyses were conducted using a 5% type I error rate. Mean ±SD and percentages were used to describe the sample and data where appropriate. Pearson's correlations (R) were calculated to determine the relationships between VAT and IL-18 in each group. Analysis of variance was used to determine differences in VAT, IL-18, and adiponectin among groups. Further, nonparametric procedures examined the differences in adiponectin among those within groups. Results Seventy-five participants were enrolled. Biomarkers above the typical concentration range were observed for VAT, IL-18, and adiponectin. Adiponectin significantly differed among groups with lower values in the diabetes group vs. the nondiabetes group. Conclusions The findings indicate that while inflammation-related biomarkers, such as adiponectin, correlate with VAT and may serve as indicators of increased risk of type 2 diabetes in FAs, correlation alone does not establish causality.